A comparison of brand loyalty between on the go and take-home consumption purchases. (March 2020) - Trinh, Giang; Dawes, John
Abstract: This paper compares consumer brand purchase loyalty for food products bought either 'on the go' (OTG), or for take-home consumption. The study uses two UK consumer packaged goods datasets. The first dataset comprises consumers' purchasing of brands in three product categories: soft drinks, crisps, and savory snacks for on the go consumption. The second contains consumers' purchasing of the same brands for take-home consumption. Analysis uses the polarization index as a behavioral loyalty measure, estimated from the Beta Binomial – Negative Binomial Distribution. This measure controls for the difference in purchase rate and brand market share across on the go and take-home. The study finds that consumer loyalty to brands is markedly higher in purchasing for on the go consumption than for take-home consumption; and that the effect is even stronger for larger brands in on the go.